2002
DOI: 10.1067/mhn.2002.122698
|View full text |Cite
|
Sign up to set email alerts
|

Duplicate Publication in the Field of Otolaryngology‐Head and Neck Surgery

Abstract: Duplicate publication is an example of inappropriate academic conduct. Because it tarnishes the reputation of the duplicating author and represents an unfair practice in terms of displacing the work of others, efforts should continue to educate authors, particularly young academicians, to avoid the practice of duplicate publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 4 publications
2
62
1
1
Order By: Relevance
“…A study of one year's publications in three general surgical journals showed that nearly 14% were duplicate or salami sliced publications 21 . Similar results have been found in an orthopaedic journal and in ENT 3,10 . Checking of references sometimes shows that arguments are supported by references to other publications which are in fact not supportive.…”
supporting
confidence: 89%
“…A study of one year's publications in three general surgical journals showed that nearly 14% were duplicate or salami sliced publications 21 . Similar results have been found in an orthopaedic journal and in ENT 3,10 . Checking of references sometimes shows that arguments are supported by references to other publications which are in fact not supportive.…”
supporting
confidence: 89%
“…publication in different languages and with clear cross references). 22,23 This might be the case found in the second instance (the article was initially published in a journal in Spanish and later the article was published in English), but the authors failed to declare the cross reference. It is possible that in the first case the authors wanted to increase visibility (the article was initially published in a SciELO-indexed journal and later it was published in a MEDLINEindexed journal).…”
Section: Discussionmentioning
confidence: 91%
“…28 Significant efforts should be made to educate authors, particularly young academicians, to avoid the practice of duplicate publication. 22,27 One limitation of the study is that we studied only the theses at one private university in Peru. Therefore, our results can not be generalised to all medical schools in Peru.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include plagiarism (Braumoeller, 2001;Monostori, 2002;Cook, 2002;Hoad, 2003;Gilbert, 2003;Pecorari, 2003;Chen, 2004;Bao, 2004), duplicate/ redundant publication (Doherty, 1996;Jefferson, 1998;Schein, 2001;Bailey, 2002;Von Elm, 2004;Mojon-Azzi, 2004;Gwilym, 2004), text/ document clustering (Maderlechner, 1997;Atlam, 2003;Dobrynin, 2004;Shin, 2004;Bansal, 2004), and information retrieval (Salton, 1991;Hui, 2004;Leuski, 2004;Muresan, 2004;Chang, 2004). These studies have shown that, in general, identifying similar documents through concept matching is quite difficult.…”
Section: Introductionmentioning
confidence: 99%